Nanogenerators in Korea - Park, Yong Tae; Choi, Dukhyun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Fossil fuels leaded the 21st century industrial revolution but caused some critical problems such as exhaustion of resources and global warming. Also, current power plants require too much high cost and long time for establishment and facilities to provide electricity. Thus, developing new power production systems with environmental friendliness and low-cost is critical global needs. There are some emerging energy harvesting technologies such as thermoelectric, piezoelectric, and triboelectric nanogenerators, which have great advantages on eco-friendly low-cost materials, simple fabrication, and various operating sources. Since the introduction of various energy harvesting technologies, many novel designs and applications as power suppliers and physical sensors in the world have been demonstrated based on their unique advantages. In this Special Issue, we would like to address and share basic approaches, new designs, and industrial applications related to thermoelectric, piezoelectric, and triboelectric devices which are on-going in Korea. With this Special Issue, we aim to promote fundamental understanding and to find novel ways to achieve industrial product manufacturing for energy harvesters.